2011
DOI: 10.1002/jsfa.4467
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fermented goats' milk containing Lactobacillus rhamnosus: in vivo study of health benefits

Abstract: Goats' milk fermented with L. rhamnosus CRL1505 could be manufactured as an alternative probiotic dairy product since this new food has the ability to stimulate the common mucosal immune system and to improve defenses against respiratory and intestinal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 52 publications
3
71
0
Order By: Relevance
“…In our laboratory, several Lactobacillus strains isolated from goatÕs milk were evaluated according to their capacity to modulate respiratory immunity and we found that Lactobacillus rhamnosus CRL1505, administered by the oral route at the proper dose, was able to increase S. pneumoniae clearance rates in lung and blood, reduce lung injuries, and increase the survival of infected mice (10). We also demonstrated that the protective effect of the CRL1505 strain can be achieved in immunocompromised malnourished mice and that it was related to an upregulation of both innate and specific immune responses in the respiratory tract (11). To elucidate the immunological mechanisms involved in the increased resistance to pneumococcal infection induced by L. rhamnosus CRL1505, we performed studies of B cell populations in BM.…”
Section: Introductionmentioning
confidence: 69%
“…In our laboratory, several Lactobacillus strains isolated from goatÕs milk were evaluated according to their capacity to modulate respiratory immunity and we found that Lactobacillus rhamnosus CRL1505, administered by the oral route at the proper dose, was able to increase S. pneumoniae clearance rates in lung and blood, reduce lung injuries, and increase the survival of infected mice (10). We also demonstrated that the protective effect of the CRL1505 strain can be achieved in immunocompromised malnourished mice and that it was related to an upregulation of both innate and specific immune responses in the respiratory tract (11). To elucidate the immunological mechanisms involved in the increased resistance to pneumococcal infection induced by L. rhamnosus CRL1505, we performed studies of B cell populations in BM.…”
Section: Introductionmentioning
confidence: 69%
“…Minervini et al (2009), developed fermented goat milk with a mixed starter culture (Streptococcus thermophilus CR12, Lactobacillus Helveticas PR4 and Lactobaillus plantarum 1288) which resulted in production of GABA, an inhibiting signal substance in the central nervous system, and provoked an in vitro ACE-inhibitory activity, which counteract high blood pressure. Recently, fermented goat milk (Lactobacillus rhamnosus CRL1505) was demonstrated to stimulate the mucosal immune system and improve the defense against intestinal and respiratory infections in a mouse immunosuppressant model (Salva et al, 2011). As mentioned above, one disadvantage with goat milk is the almost nonexistent content of folic acid.…”
Section: Effect On Infancy Intakementioning
confidence: 99%
“…Some few studies reported that nasally administered heat-killed immunobiotics are capable of improving resistance against respiratory pathogens (50, 61, 84, 85) (Table 1). In this regard, studies by Hori et al (50) showed that the nasal priming with heat-killed L. casei Shirota significantly augmented the resistance of adult BALB/c mice to influenza virus by stimulating respiratory tract cellular immunity.…”
Section: Local Modulation Of Respiratory Anti-viral Immunity By L Rhmentioning
confidence: 99%